Improving Community Understanding Through Socialization, Literature and Education of Sharia Banking in the City of Palangkaraya, Central Kalimantan - Achmad, Aditya; Sadikin, Ali; Sukmana, Enriko Tedja; Misra, Isra; Adlina, Fadiah; Hasnita; Iqbal, Muhammad; Safitri, Nadia; Aldianto, Asrofi (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service focuses on the lack of public knowledge of Islamic banking in Indonesia so that socialization, literacy, and education activities are needed for Micro, Small, and Medium Enterprises (UMKM). The expected goal is none other than to increase UMKM related to Islamic banking, both systems, products, and mechanisms so that it has an impact on public interest in using Islamic banking services in Central Kalimantan. The UMKM involved in the service activities are UMKM in Kereng Bangkirai Village as many as 55 UMKM and 5 employees of Bank Syariah Indonesia Palangka Raya Branch. The method used in this service is Community Based Articipatory Research where the service is carried out by involving stakeholders with Focus Group Discussion (FGD) activities. The results of the service show that by carrying out community-based service activities and involving stakeholders, especially banking, the public's understanding of Islamic banking is increasing. These activities also have an impact on the community, especially UMKM, to use Islamic banking services.